2022
DOI: 10.1038/s41598-022-21513-9
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin D status and severity of COVID-19

Abstract: We explored the association between COVID-19 severity and vitamin D status using information from Danish nation-wide health registers, the COVID-19 surveillance database and stored blood samples from the national biobank. 25-hydroxyvitamin D (25(OH)D) was measured using tandem mass spectroscopy. The association between 25(OH)D levels and COVID-19 severity, classified hierarchical as non-hospitalized, hospitalized but not admitted to an intensive care unit (ICU), admitted to ICU, and death, was evaluated by pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
(85 reference statements)
1
15
0
1
Order By: Relevance
“…A recent review by Martineau and Cantorna [ 848 ] reported that out of 11 randomized controlled trials that had been published at the time of writing, only 4 reported significant associations. Two recent large studies and a systematic review on vitamin D supplementation reported lower severity and mortality in the treated groups compared to controls [ 854 , 855 , 856 ], a study using Mendelian randomization found no association between genetically predicted 25(OH)D levels and COVID-19 severity [ 857 ], and another genetic analysis demonstrated an association between a risk score constructed from several genetic variants that influence vitamin D pathways and with 25(OH)D levels, and between 25(OH)D levels with disease outcome [ 858 ]. Recently, a mechanistic link has been proposed between vitamin D supplementation and reduced COVID-19 severity through the increased expression of interferon stimulating genes and higher protein levels both in vitro and in vivo [ 859 ].…”
Section: Host Factorsmentioning
confidence: 99%
“…A recent review by Martineau and Cantorna [ 848 ] reported that out of 11 randomized controlled trials that had been published at the time of writing, only 4 reported significant associations. Two recent large studies and a systematic review on vitamin D supplementation reported lower severity and mortality in the treated groups compared to controls [ 854 , 855 , 856 ], a study using Mendelian randomization found no association between genetically predicted 25(OH)D levels and COVID-19 severity [ 857 ], and another genetic analysis demonstrated an association between a risk score constructed from several genetic variants that influence vitamin D pathways and with 25(OH)D levels, and between 25(OH)D levels with disease outcome [ 858 ]. Recently, a mechanistic link has been proposed between vitamin D supplementation and reduced COVID-19 severity through the increased expression of interferon stimulating genes and higher protein levels both in vitro and in vivo [ 859 ].…”
Section: Host Factorsmentioning
confidence: 99%
“…Over 29% of children in our nation lack adequate levels of vitamin D (15). Reduced circulating 25(OH)D concentrations have also been linked to Covid-19 severity and the risk of contacting the infection, according to reports (16). The outcome is more severe in some instances.…”
Section: Methodsmentioning
confidence: 99%
“…Vitamin D (vit D) deficiency is identified as one of the most conspicuous nutritional risk factors that can potentially influence the disease progression and mortality rate. 9 Several studies reported that a lower serum level of vit D was associated with a higher COVID-19 infection rate and worse outcomes in these patients, for instance, an increased mortality rate. 10 Vit D is a steroid hormone endogenously produced on the skin following exposure to the ultraviolet radiation of the sun.…”
Section: Introductionmentioning
confidence: 99%
“…At present, one of the most imperative ways to deal with this disease is to control risk factors. Vitamin D (vit D) deficiency is identified as one of the most conspicuous nutritional risk factors that can potentially influence the disease progression and mortality rate 9 . Several studies reported that a lower serum level of vit D was associated with a higher COVID‐19 infection rate and worse outcomes in these patients, for instance, an increased mortality rate 10 …”
Section: Introductionmentioning
confidence: 99%